Preparation of ethylene glycol dimethacrylate (EGDMA)-based terpolymer as potential sorbents for pharmaceuticals adsorption - Shaipulizan, Nur Syafiqah; Md. Jamil, Siti Nurul Ain; Kamaruzaman, Sazlinda; Subri, Nur Nida Syamimi; Adeyi, Abel Adekanmi; Abdullah, Abdul Halim; Abdullah, Luqman Chuah (MDPI, 2020)
Ethylene glycol dimethacrylate (EGDMA) is used as a crosslinker in poly(acrylonitrile (AN)-co-vinylbenzyl chloride (VBC)) to investigate the effect of long-chain crosslinker to the porosity of the terpolymer system. Poly(AN-co-EGDMA-co-VBC) is synthesized by using precipitation polymerization method and further hypercrosslinked by Friedel-Crafts reaction. FT-IR spectra of poly(AN-co-EGDMA-co-VBC) show that the absorption bands at ~1290 cm−1 that are assigned to the C–Cl vibrations are almost disappeared in hypercrosslinked (HXL) poly(AN-co-EGDMA-co-VBC) polymers, confirming that the hypercrosslinking reaction is successful. SEM images show that the morphologies of the polymers are retained through the hypercrosslinking reactions. Brunauer–Emmett–Teller (BET) analysis shows that hypercrosslinked polymers had a specific surface area up to 59 m2·g−1. The preliminary performance of the terpolymer adsorbent to capture polar analyte is evaluated by adsorbing salicylic acid and mefenamic acid from aqueous solution in a batch system. The maximum adsorption capacity of salicylic acid and mefenamic acid were up to 416.7 mg·g−1 and 625 mg·g−1, respectively, and the adsorption kinetic data obeyed pseudo-second-order rate equation.